2022
DOI: 10.1001/jamanetworkopen.2021.48940
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intraindividual Difference in Estimated Glomerular Filtration Rate by Creatinine vs Cystatin C and End-stage Kidney Disease and Mortality

Abstract: IMPORTANCEAs cystatin C is increasingly adopted to estimate glomerular filtration rate (eGFR), clinicians will encounter patients in whom cystatin C-based eGFR (eGFRcys) and creatinine-based eGFR (eGFRcr) differ widely. The clinical implications of these differences, eGFRdiff cys-cr , are unknown. OBJECTIVE To evaluate the associations of eGFRdiff cys-cr with end-stage kidney disease (ESKD) and mortality among individuals with chronic kidney disease (CKD). DESIGN, SETTING, AND PARTICIPANTSThis is a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 46 publications
3
35
0
Order By: Relevance
“…These differences between eGFRcr and eGFRcys are prognostic of ESKD, hospitalization, CVD, and mortality. [39][40][41] For an individual patient, the interpretation of the various eGFR estimates is crucial for clinical decisionmaking. Below, we present cases that highlight such clinical scenarios.…”
Section: Approach To Patients With Discrepant Egfrs By Cystatin C Vs ...mentioning
confidence: 99%
See 3 more Smart Citations
“…These differences between eGFRcr and eGFRcys are prognostic of ESKD, hospitalization, CVD, and mortality. [39][40][41] For an individual patient, the interpretation of the various eGFR estimates is crucial for clinical decisionmaking. Below, we present cases that highlight such clinical scenarios.…”
Section: Approach To Patients With Discrepant Egfrs By Cystatin C Vs ...mentioning
confidence: 99%
“…Emerging research implicates that CysC may have additional value when measured longitudinally within an individual and in the context of transplant nephrology. Chen et al 39 has shown that among individuals with CKD, those with faster decline in eGFRcys relative to eGFRcr had higher risk of progression to ESKD and mortality compared to individuals in whom the two eGFRs declined in parallel.…”
Section: Future Potential Use Of Cystatin Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent evidence suggests that there are often large discrepancies between eGFR solely based on creatinine (eGFR cr ) and that based on cystatin C (eGFR cys ). [7][8][9][10] Studies have suggested that intraindividual discrepancies between eGFR cys and eGFR cr are associated with adverse outcomes, 7,9,11 with a worse prognosis for individuals who have an eGFR cys that is lower than eGFR cr . However, it is unknown whether this difference reflects better estimation of GFR or merely captures additional confounders (e.g., inflammation).…”
Section: Introductionmentioning
confidence: 99%